A matched cohort examination of publication rates among clinical subspecialty fellows enrolled in a translational science training program. Issue 5 (5th February 2019) - Ehlers, Shawna L.; Cornelius, Katherine E.; Greenberg-Worisek, Alexandra J.; Warner, David O.; Weavers, Karen M.; Thomson, Kelly R.; Hansen, Marissa J.; Larson, Joseph J.; Enders, Felicity T.; Iyer, Prasad G.
Abstract: Purpose: This study examined the effectiveness of a formal postdoctoral education program designed to teach skills in clinical and translational science, using scholar publication rates as a measure of research productivity. Method: Participants included 70 clinical fellows who were admitted to a master's or certificate training program in clinical and translational science from 1999 to 2015 and 70 matched control peers. The primary outcomes were the number of publications 5 years post-fellowship matriculation and time to publishing 15 peer-reviewed manuscripts post-matriculation. Results: Clinical and translational science program graduates published significantly more peer-reviewed manuscripts at 5 years post-matriculation (median 8 vs 5, p =0.041) and had a faster time to publication of 15 peer-reviewed manuscripts (matched hazard ratio = 2.91, p =0.002). Additionally, program graduates' publications yielded a significantly higher average H-index (11 vs. 7, p =0.013). Conclusion: These findings support the effectiveness of formal training programs in clinical and translational science by increasing academic productivity.